Leonidas Karakatsanis, Turkish-Greek Relations: Rapprochement, Civil Society and the Politics of Friendship - Derisiotis, Anthony (Historein, 2019)
Review of Leonidas Karakatsanis, Turkish-Greek Relations: Rapprochement, Civil Society and the Politics of Friendship. London and New York: Routledge, 2014. xxi + 283 pp.